Mycophagy varies at individual-, population- and site- levels in the diet of a translocated mammal across multiple safe havens - A. Naccarella; C. Truong; E. G. Ritchie; D. R. Sutherland; A. Coetsee; A. R. Rendall (Biodiversity and Conservation, 2026)
Restoring ecosystem functions via conserving and translocating threatened species is an increasingly common conservation action and priority. Monitoring how a translocated species interacts with the recipient ecosystem and co-occurring species is rarely the focus of strategic management plans. Digging, mycophagous mammals play critical ecosystem roles including bioturbation and fungal spore dispersal. The fungal diets of translocated digging-mycophagous mammals have rarely been investigated across translocation sites. We examined the endangered eastern barred bandicoot ( Perameles gunnii ) as a case study to compare the ecological role of a generalist mycophagous mammal that has been translocated to multiple sites inside and outside their historic range for conservation purposes in Australia. We characterized fungal assemblages in 91 bandicoot scats across five sites, two inside and three outside the species historic range, using ITS2 metabarcoding. Despite low sample size, our data suggested fungal richness and community composition varied at individual-, population- and site- levels, aligning with the opportunistic and generalist dietary niche of bandicoots. We found no clear trends between fungal richness or community composition with vegetation attributes. Our study highlights the need to understand how mammal-fungi interactions vary across spatial-scales and population-levels to better predict possible ecological impacts of conservation translocations and restoration attempts. We highlight the challenges of studying environmental drivers of mycophagy in modified landscapes, particularly with limited reference ecosystems. We therefore encourage integrated and explicit monitoring of key species interactions at an individual-, population- and site-level to better understand synergies between translocations for species conservation and the reinstatement of ecosystem functions.